Centrifugal Lithography: Self‐Shaping of Polymer Microstructures Encapsulating Biopharmaceutics by Centrifuging Polymer Drops. Issue 19 (13th July 2017) - Yang, Huisuk; Kim, Suyong; Kang, Geonwoo; Lahiji, Shayan F.; Jang, Mingyu; Kim, Young Mi; Kim, Jae‐Myung; Cho, Sang‐Nae; Jung, Hyungil
Abstract: Polymeric microstructures encapsulating biopharmaceutics must be fabricated in a controlled environment to preserve the biological activity. There is increasing demand for simple methods designed to preserve the biological activity by utilizing the natural properties of polymers. Here, the paper shows that centrifugal lithography (CL) can be used for the fabrication of such microstructures in a single centrifugation, by engineering the self‐shaping properties of hyaluronic acid (HA). In this method, HA drops are self‐shaped into hourglass‐microstructures to produce two dissolving microneedles (DMN), which facilitate transdermal delivery via implantation on the skin. In addition, tuberculin purified protein derivatives are encapsulated into HA DMNs under refrigerated conditions (4 °C) during CL. Therefore, the tuberculin skin test (TST) with the DMNs indicates minimal damage, as opposed to the case of TST with traditional hypodermic needles. These findings on the fabrication of polymeric microstructures with biopharmaceutics may trigger the development of various biomedical devices and therapies. Abstract : Centrifugal lithography (CL) enables fabrication of polymer microstructures via self‐shaping during a centrifugation under controlled environment for biopharmaceutics. Dissolving microneedle (DMN) array composed of hyaluronic acid and tuberculin purified protein derivatives (PPD) is fabricated by CL under refrigerated conditions (4 °C) to preserve PPD. Diagnosis of tuberculosis with the DMNs indicates minimal damage, as opposed to the traditional hypodermic needles.